A Rare Presentation of Avulsion Amputation of the Ring Finger Managed by Double Cross Finger Flap: Prognosis and Diagnosis - Gopalakrishna, Annavarapu (Medical Research and Its Applications Vol. 1, 2024)
The study presents a rare case of avulsion amputation of the ring finger managed by a double cross-finger flap. Avulsion amputation of the fingers is rare. The current trend is to replant the avulsed tissue in spite of a high rate of failure. We report a case of a 33-year-old right-handed male small-time businessman presented with a history of injury to his left ring finger. His ring was caught in some part of a bus as he alighted and the bus moved forward pulling off his finger. There are situations where replantation is not possible. Various salvage procedures have been mentioned. A similar procedure has been reported by other authors but with a short-term follow-up. Many procedures are available for the salvage of a nonreplantable ring avulsion injury. In our hands, the simple procedure of cross-finger flaps has given a good long-term result.